The Investigation of Acetylation and Anti-Oxidant Effect on Weathering of wood Plastic Composites By Means of FTIR and Color Metry (Color measurement) - Pyvand Darabi (Regional Information Center for Science and Technology (RICeST), 2010)
In this study capability of acetylated poplar flour in manufacture of high density poly ethylene composite which expose to accelerated weathering, was investigated. The acetylation degrees at medium and zero (control) levels, use of anti- oxidant and duration of weathering were considered as variables and their effects on discoloration and photodegradation of WPC were investigated. To determine treatments influence on changes and color fade resulting from weathering, samples were tested after o, 250, 2000 hours of weathering. The results indicated that application of acetylated wood flour in WPC can reduce about 25% of weathering discoloration in short time and about 17% in long time. Also it shows that as exposed time of weathering increase Anti oxidant loss its effect. Although in short time it can reduce 12% of weathering color changes. FTIR results show that after 2000 h of weathering all peaks samples had same decrease which mean none of the treatments were useful. But Anti oxidant can reduce depth of weathering.